2023
DOI: 10.3390/plants12101926
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Two Olive Cultivars to Salt Stress

Abstract: The olive tree (Olea europaea L.) is the main fruit tree in most of the arid and semi-arid regions of Tunisia, which is where the problem of salinity is more pronounced. Salinity is one of the main factors that affects the productivity of olive trees, so the objective of this experiment was to study the effects of salinity on the photosynthesis, water relations, mineral status, and enzymatic activity of two cultivars of Olea europaea L., ‘Chemlali’ and ‘Koroneiki’. The trial was conducted under controlled cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…In most of the cultivars studied there is a decrease in CO2 assimilation with 100 mM NaCl [20,52,54,73,122,133,[137][138][139]. It has been reported that there is greater inhibition of CO2 assimilation rate in olive cultivars with high rates of photosynthesis and stomatal conductance [57,122,139,140]. In several studies it has been observed that photosynthesis inhibition is lower in the more tolerant cultivars compared to the more sensitive ones [57,122].…”
Section: Physiological Adaptationmentioning
confidence: 99%
See 4 more Smart Citations
“…In most of the cultivars studied there is a decrease in CO2 assimilation with 100 mM NaCl [20,52,54,73,122,133,[137][138][139]. It has been reported that there is greater inhibition of CO2 assimilation rate in olive cultivars with high rates of photosynthesis and stomatal conductance [57,122,139,140]. In several studies it has been observed that photosynthesis inhibition is lower in the more tolerant cultivars compared to the more sensitive ones [57,122].…”
Section: Physiological Adaptationmentioning
confidence: 99%
“…Salt stress tolerance is a multigenic trait in which different mechanisms are involved [48,49]. Olive is considered moderately tolerant to salinity [50], although differences in response to salt stress have been observed between cultivars [51][52][53][54][55][56][57].…”
Section: Mechanisms Of Olive Tolerance To Salt Stressmentioning
confidence: 99%
See 3 more Smart Citations